2015
DOI: 10.1080/19345747.2014.911396
|View full text |Cite
|
Sign up to set email alerts
|

Covariate Balance in Bayesian Propensity Score Approaches for Observational Studies

Abstract: Bayesian alternatives to frequentist propensity score approaches have recently been proposed. However, few studies have investigated their covariate balancing properties. This article compares a recently developed two-step Bayesian propensity score approach to the frequentist approach with respect to covariate balance. The effects of different priors on covariate balance are evaluated and the differences between frequentist and Bayesian covariate balance are discussed. Results of the case study reveal that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…A further study of the covariate balance properties of the Kaplan and Chen (2012) approach was given in a case study by Chen and Kaplan (2014). Their results revealed that both Bayesian and frequentist propensity score approaches substantially reduced initial imbalance as expected, and their performance on covariate balance was similar with regard to the standardized mean/proportion differences and variance ratios in the treatment group and control group.…”
Section: A Two-step Bayesian Propensity Score Analysismentioning
confidence: 78%
See 1 more Smart Citation
“…A further study of the covariate balance properties of the Kaplan and Chen (2012) approach was given in a case study by Chen and Kaplan (2014). Their results revealed that both Bayesian and frequentist propensity score approaches substantially reduced initial imbalance as expected, and their performance on covariate balance was similar with regard to the standardized mean/proportion differences and variance ratios in the treatment group and control group.…”
Section: A Two-step Bayesian Propensity Score Analysismentioning
confidence: 78%
“…Chen and Kaplan (2014) argued that a benefit of conducting Bayesian propensity score analysis is that one can obtain the posterior distribution of the propensity score and thus the posterior distribution of corresponding balance indices (e.g., Cohen’s d and variance ratio) so that the variation in balance indices can be studied in addition to the point estimates to assist in balance checking. Good balance is achieved if both the point estimates and the posterior probability intervals of the balance indices fall into the desirable range.…”
Section: A Two-step Bayesian Propensity Score Analysismentioning
confidence: 99%
“…Several authors (see Austin 2011; Chen and Kaplan 2015) note the fact that the use of propensity score adjustment as a conditioning method can be hindered by possible model misspecification. The credibility of propensity score analysis is based on the assumption of ''strongly ignorable treatment assignment'' where it is assumed that all of the relevant covariates are included in the treatment assignment and that the bias due to unmeasured covariates is ignorable (see Lanehart et al 2012, p. 8).…”
Section: Ps-ancova and Model Specificationmentioning
confidence: 99%
“…Propensity score stratification involves forming strata directly on the basis of the observed propensity score. Subclassification into five strata on continuous distributions such as the propensity score has been shown to remove approximately 90 % of the bias due to non-random selection effects ( Cochran 1968 , see also Rosenbaum and Rubin 1983 ). However, for stratification on the propensity score to achieve the desired effect, the assumption of no hidden biases must hold.…”
Section: Implementation Of the Propensity Scorementioning
confidence: 99%